The Role of Lifestyle in the Prevention and Treatment of Insulin Resistance: A Review of Clinical and Intervention Studies - Rybak, Daria; Krupa, Olga; Furtak, Kinga; Wójcik, Zofia Martyna; Romańczuk, Kuba Borys; Stolarczyk, Szymon Przemysław; Pietrukaniec, Paulina Dorota; Omasta, Bartosz; Kamińska-Omasta, Katarzyna; Czerska, Magdalena Agata (Quality in Sport, 2025)
Introduction Insulin resistance (IR) is a metabolic disorder characterized by reduced tissue sensitivity to insulin, resulting in impaired glucose homeostasis. IR plays a pivotal role in the development of type 2 diabetes, metabolic syndrome, and associated cardiovascular complications. Effective strategies for the prevention and treatment of IR focus on lifestyle modification, including physical activity and stress management. Aim of the Study The aim of this study is to evaluate the role of lifestyle factors in the prevention and treatment of insulin resistance (IR) based on the analysis of clinical and interventional studies, with a particular focus on dietary interventions, physical activity programs, stress reduction techniques, and sleep quality improvement recommendations. Materials and Methods A review of clinical and interventional studies was conducted using databases such as PubMed. The analysis included studies evaluating the impact of specific lifestyle interventions on markers of insulin resistance (IR), such as fasting insulin levels, HOMA-IR indices and glucose tolerance. Particular attention was paid to randomized controlled trials (RCTs) and meta-analyses published between 2020 and 2024. Summary Studies have shown that diets such as the Mediterranean and DASH, combined with regular aerobic and resistance exercises, significantly improve insulin sensitivity. Additionally, stress-reduction techniques like mindfulness and yoga, along with adequate sleep quality, enhance positive metabolic effects. These findings highlight the need for a multifaceted approach to treating insulin resistance, incorporating dietary and behavioral changes. The review also points out research gaps and emphasizes the necessity of long-term studies to refine lifestyle recommendations for diverse populations